Efeito do treinamento de força excêntrica no controle autonômico da freqüência cardíaca de idosos durante o repouso e contrações isométricas - Takahashi, Anielle Cristhine de Medeiros (2007)
The purpose of the present study was to investigate the effect of eccentric strength training (ST) on autonomic control of heart rate (HR) evaluated at rest and during isometric exercise. Nine healthy men (62 ±2 years old) were submitted to 12 weeks of ST for knee extensors and flexors muscles (2x/week, 2-4 series of 8-12 repetitions, 70-80% of eccentric peak torque). Before and after the ST, the HR and its variability were evaluated at rest (supine and seated conditions) and during the sub-maximal isometric contractions (SIC; 15, 30 and 40% of maximal voluntary contraction) of knee extension wich were performed during 240s or until exhaustion. The HR was obtained at pre- (60s), during and post SIC (120s). Then, the variation (∆) between the resting HR and HR at 10, 30, 60s and end of contraction observed during each SIC was analyzed. The HR variability was evaluated by the RMSSD index, which was determined in resting condition and during SIC (i.e., two windows of 30s in duration at the beginning and end of R-R interval data). The ANOVA two-way (repeated measures) and t-test was utilized for statistical analysis (p < 0.05). The ST increased the eccentric torque (extension: 210 ± 38 to 252.7 ± 61 N.m, flexion: 117.6 ± 25.1 to 133 ± 27.3 N.m) , but did not change the HR and HR variability at rest (HR supine: 62 ± 11 to 65 ± 9 bpm, HR seated: 62 ± 11 to 66 ± 9, RMSSD supine: 28.5 ± 18 to 21.5 ± 8.4, RMSSD seated: 30.4 ± 2 to 18.9 ± 6.2). The ST did not modify the isometric peak torque (177.6 ± 25 to 195.2 ± 31,2 N.m) and the time of execution of each SIC (15%: 240 to 240s, 30%: 203.4 ± 55 to 218 ± 5s, 40%: 135.6 ± 56.7 to 144.6 ± 55.6s). During the SIC, the pattern of HR response (significative increase in ∆HR from 30s to the end of contraction in 15 and 40%) and the RMSSD index (significative decrease from the first 30s to the last 30s of contraction in all levels of effort) was similar for the pre- and post training. Despite the ST increased the eccentric torque, it did not generate changes in the autonomic control of heart rate at rest and during the SIC.